Globe tenting: a sign of increased orbital tension. - Dalley, R W; Robertson, W D; Rootman, J (American Journal of Neuroradiology, 1989)
Globe tenting is a change in the posterior globe configuration that results in a tented or conical appearance and is objectively defined as a posterior globe angle of less than 130 degrees. Globe tenting is caused by an acute/subacute intraorbital mass effect producing significant proptosis with tethering of the globe by the stretched optic nerve. In this series of 10 patients, globe tenting was produced by subperiosteal abscess (five cases), hemorrhage into a lymphangioma (two cases), a varix (one case), traumatic carotid hemorrhage into a lymphangioma (two cases), a varix (one case), traumatic carotid cavernous fistula (one case), and multiple epithelial implantation cysts (one case). Progressive narrowing of the posterior globe angle correlated with an increase in proptosis and in optic nerve length, as well as with more severe visual impairment. Tenting with a posterior globe angle of 120-130 degrees correlated with mild visual symptoms and a good recovery. A posterior globe angle of less than 120 degrees with acute proptosis constitutes a surgical emergency; a delay in surgical decompression in these patients may prevent complete recovery of visual function. CT is useful in providing good characterization of globe tenting and, thus, in helping to determine the clinical significance of this abnormality.